Respuesta :

34091
(x+3)^2+(y-4)^2=49
If you need clarification, you can ask me.

Answer:

  [tex](x+3)^2+(y-4)^2=49[/tex]

Step-by-step explanation:

Given : [tex]x^2+y^2=49[/tex]

To Find: Write an equation for the translation of [tex]x^2+y^2=49[/tex]   by 3 units left and 4 units up.

Solution:

[tex]x^2+y^2=49[/tex]

[tex]y^2=49-x^2[/tex]

[tex]y=\sqrt{49-x^2}[/tex]

So, [tex]f(x)=y=\sqrt{49-x^2}[/tex]

We are given that first is shifted towards 3 units left.

If the given function f(x) translated by b units left then

f(x)→f(x+b)

So, [tex]f(x)=\sqrt{49-x^2}[/tex] translated by 3 units left

So, [tex]f(x)=\sqrt{49-x^2}[/tex] → [tex]f(x+3)=\sqrt{49-(x+3)^2}[/tex]

Now it is again translated by 4 units up.

If the given function f(x) translated by b units up then

f(x)→f(x)+b

[tex]f(x+3)=\sqrt{49-(x+3)^2}[/tex]→ [tex]f(x+3) +4 =\sqrt{49-(x+3)^2 }+4[/tex]

So, the function becomes : [tex]f(x)=y=\sqrt{49-(x+3)^2 }+4[/tex]

                                              [tex]y-4=\sqrt{49-(x+3)^2 }[/tex]  

                                              [tex](y-4)^2=49-(x+3)^2[/tex]  

                                              [tex](x+3)^2+(y-4)^2=49[/tex]

Hence an equation for the translation of [tex]x^2+y^2=49[/tex]   by 3 units left and 4 units up is     [tex](x+3)^2+(y-4)^2=49[/tex]